Studies in African music: volume II - Jones, A. M. (London Oxford university press, 1959)
Studies in African Music is a 1959 book in two volumes by A.M. Jones. It is an in-depth analysis of the traditional music of the Ewe tribe.The work is divided into two volumes,with the first volume being an analysis of the music presented in Volume II, and the second being full-score reproductions of the pieces in question.Volume I Contents:IntroductionPlay-Songs and Fishing SongsThe Instruments of the OrchestraThe Nyayito DanceYeve Cult MusicClub Dances - The Adzida DanceThe Social Dance - AgbadzaA Comparison of DrummingThe Homogeneity of African MusicTone and TuneThe Neo-Folk-MusicVolume II Contents:Play-Songs and Fishing SongsThe Nyayito DanceYeve Cult Music: (a) The Husago Dance, (b) The Sovu Dance, (c) The Sogba DanceThe Adzida DanceThe Agbadza DanceThe Icila Dance
Keywords: Ethnomusicology; Africa